Faktor Pejamu (Host) yang Berhubungan dengan Kejadian Tuberkulosis Paru - Adinda Wulan Adha; Umi Romayati Keswara; Rudi Winarno (Malahayati Nursing Journal, 2024)
ABSTRACT Pulmonary tuberculosis is a contagious infectious disease caused by mycobacterium tuberculosis that enters the body through the respiratory tract, gastrointestinal tract and open wounds on the skin, but most often through inhalation of droplets from patients with pulmonary tuberculosis. There were 278 patients suspected of having pulmonary tuberculosis at the Rajabasa Indah (RBI) Health Center in Bandar Lampung City. This study was to identify the factors of host concerning lung tuberculosis incidences at Rajabasa Indah Primary Health Care (Puskes RBI) of Bandar Lampung City in 2023. The study used quantitative method with analytical design and cross sectional approach. The population of the study was registered patients taking tuberculosis examination and investigation at Rajabasa Indah Primary Health Care in 2023. There were 278 suspected patients but the samples were 164 respondents. The sampling technique was purposive. The data analysis was through chi square. Based on the frequency distribution of respondents with pulmonary tuberculosis 3.7%, respondents with productive age 73.8%, and respondents with female gender 47.0%. Based on bivariate analysis, it was found that age variable (p-value 0.381) and gender variable (p-value 0.569). There is no relationship between age and gender with the incidence of pulmonary tuberculosis at the Rajabasa Indah Health Center (RBI) in Bandar Lampung City in 2023. For the puskesmas it is recommended to document complete medical record data, provide counseling about tuberculosis and be able to collaborate with researchers in carrying out research.  Keywords: Lung Tuberculosis, Host Factors  ABSTRAK Tuberkulosis paru adalah penyakit infeksi menular yang disebabkan mycobacterium tuberculosis yang masuk ke dalam tubuh melalui saluran pernafasan, saluran pencernaan dan luka terbuka pada kulit, namun paling sering melalui inhalasi droplet dari penderita tuberkulosis paru. Terdapat 278 pasien yang diduga menderita tuberkulosis paru di Puskesmas Rajabasa Indah (RBI) Kota Bandar Lampung. Diketahui hubungan antara faktor pejamu (host) dengan kejadian tuberkulosis paru di Puskesmas Rajabasa Indah (RBI) Kota Bandar Lampung tahun 2023. Menggunakan desain analitik kuantitatif dengan pendekatan crosssectional. Populasinya adalah pasien poli tuberkulosis yang menjalani pemeriksaan dan pengecekan tuberkulosis di Puskesmas Rajabasa Indah (RBI) Kota Bandar Lampung tahun 2023 berjumlah 278 pasien terduga tuberkulosis dengan sampel 164 responden menggunakan teknik purposive sampling. Analisis data menggunakan uji statistik chi-square. Berdasarkan distribusi frekuensi responden dengan tuberkulosis paru 3,7%, responden dengan usia produktif 73,8%, dan responden dengan jenis kelamin perempuan 47,0%. Berdasarkan analisa bivariat didapatkan variabel usia (p-value 0,381) dan variabel jenis kelamin (p-value 0,569). Tidak ada hubungan usia dan jenis kelamin dengan kejadian tuberkulosis paru di Puskesmas Rajabasa Indah (RBI) Kota Bandar Lampung tahun 2023. Bagi pihak puskesmas disarankan untuk mendokumentasikan data rekam medis secara lengkap, memberikan penyuluhan tentang tuberkulosis dan dapat menjalin kerjasama dengan pihak peneliti dalam melaksanakan penelitian. Kata Kunci: Tuberkulosis Paru, Faktor Pejamu (Host).